ICT infrastructure and economic growth : evidence from Asean-5 using panel dynamic OLS analysis - Mohd Mahyideen, Jamilah; Ismail, Normaz Wana (2012)
In this study, we investigate empirically the contribution of information and communications technologies (ICT) infrastructure, in affecting economic growth in selected ASEAN countries over the period 1980-2009. The studies of ICT infrastructure have received so much attention in recent studies due to its potential role to contribute to more rapid growth and productivity gains. However, empirical evidences on the importance of ICT infrastructure for growth performance, particularly for ASEAN countries, have been very scarce in the literature. This study examines the contribution made by ICT using more recent data. The availability of ICT infrastructure is captured by fixed line mobile phone subscribers (per 100 inhabitants). In addition, this study also includes another two measures of ICT which are mobile cellular subscription (per 100 inhabitants) and internet users (per 100 inhabitants). By employing panel dynamic OiS (DOLS) regression methods, the results suggest a significant and positive correlation for all three variables that capture ICT infrastructure. The study concluded that ICT infrastructure indeed a key driver for ASEAN growth performance.